(untitled) (Academia Journal of Medicine, 2026)
Background: Preemptive analgesia refers to the administration of analgesic medication before a painful stimulus in order to reduce postoperative pain. This approach helps bridge the time gap between the onset of action of analgesic agents and the waning effect of local anesthesia. Previous studies have also highlighted the role of central sensitization, a condition characterized by increased responsiveness of the nervous system to noxious stimuli, which can intensify postoperative pain. Administration of analgesics prior to the procedure may help prevent central sensitization and provide improved postoperative pain control. Aim: To evaluate the effect of preoperative administration of etoricoxib 90 mg on postoperative pain following extraction of a single mandibular third molar. Material and Method: A double-blinded prospective observational study was conducted on 50 patients undergoing extraction of a single mandibular third molar. Participants were divided into two groups: the study group received tablet etoricoxib 90 mg 30 minutes prior to the procedure, while the control group received a placebo. Postoperative pain intensity was assessed using a visual analog scale (VAS) at 1 hour, 6 hours, 12 hours, and 24 hours after the extraction. The results were analyzed using the independent samples t-test. Results: Patients who received etoricoxib reported lower postoperative pain scores compared with the placebo group at all evaluation intervals. The difference in pain intensity was most notable during the early postoperative period and gradually decreased over time, although the study group consistently demonstrated lower VAS scores than the control group throughout the 24-hour observation period. Conclusion: Preemptive administration of etoricoxib 90 mg prior to mandibular third molar extraction can effectively reduce postoperative pain compared with placebo, particularly during the early postoperative phase. This approach may serve as a useful strategy for improving postoperative pain management in dental extraction procedures.